Internationalization Narratives: An External Reputation or Higher Education’s Culture? (Dramaturgy Study Of Cultural Performance) - Hadiputri, Desisonia Lilia; Trenggono, Nanang; Ashaf, Abdul Firman; Wardhani, Andy Corry (Jurnal Komunikasi, 2025)
Internationalization narrative in Indonesia commonly mentioned in the national forum whether by political elites or ministry of education & culture. Those indicated that the government has already understood about the urgency of Higher Education (HE) in creating high-competitive human resources towards globalization era. Directorate General HE envisions world-class universities not only by rankings but through a quality culture, academic culture, and work culture. However, practically, developing region such as Lampung province has some issues in defining internationalization within their institutions. The purpose of the research is to desribe how higher education elite construct the front and back stage meaning of internationalization. The research, based on Schein's Organizational Culture and Pacanowsky and Trujillo's Communication Performance models, utilized phenomenological methods including in-depth interviews towards key informans, observations, and document analysis. Findings indicate alignment between Universitas Lampung (Unila)'s leadership assumptions and internationalization: globalization as certainy, international recognition orientation, and the significance of leadership in global competition. Key values promoted include dignity in equality, prestige, local wisdom, and global awareness. Internationalization is interpreted as striving for World Class University status. The study confirms through dramaturgy theory that Unila demonstrates leadership commitment and uses prestige rhetoric to unify leaders, though enculturation and global awareness are lacking, resulting in low student engagement in international programs. World Class University is seen as a dynamic expression of institutional image and reputation, facing various challenges.